The Payung and the Rising Sun: A Study of Javanese Pangreh Raja during the Japanese Occupation - Bahtiar Effendy (Studia Islamika, 2009)
This study is a preliminary attempt to reconstruct and analyze the pangreh praja's social and political role, if any, during the Japanese occupation. Emphasis will be put on a critical assessment of the Japanese attitude toward the pangreh praja, and the pangreh praja's relationship with the nationalists, and the general populace. Through such examinations, it is expected that each of their roles can be assessed. The historical roots of thepangreh prajareach back to Dutch colonial history. It is often dated as early as the first installation of the o?ce of the Javanese regents. Such a view seems to be easy to understand as the regents were placed in the highest position in the pangreh praja's administrative hierarchy.DOI: 10.15408/sdi.v16i3.473